IMPLEMENTATION OF TEACHING AND LEARNING APPROACHES OF INFANT AND TODDLERS IN CHILDCARE CENTRES (TASKA): A CASE STUDY ON MEETING THE ASPIRATION OF TODAY’S PARENTS - NUR PUTRI SABARINA RAMLI; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study examines the implementation of teaching and learning approaches for infants and toddlers in Malaysian childcare centres (TASKA) and how these approaches meet the aspirations of today’s parents. Using a library research method, relevant articles, policies, and reports were reviewed to identify effective practices in early childhood care and education (ECCE). The findings highlight play-based learning, responsive caregiving, and sensory exploration as key approaches that promote holistic development while aligning with parents’ expectations for safe, nurturing, and developmentally balanced environments. Guided by Developmentally Appropriate Practice (DAP) and Bronfenbrenner’s Ecological Systems Theory, the study emphasizes the importance of age-appropriate, culturally responsive, and relational teaching. However, challenges remain in areas such as teacher quality and inconsistencies between public and private TASKA. Recommendations include strengthening teacher professional development, promoting family and community collaboration, and ensuring consistent quality standards across all centres. These efforts are essential for building nurturing, engaging, and developmentally appropriate environments that meet modern parents’ expectations and support the overall growth of Malaysia’s youngest learners Keywords: TASKA, Early Childhood Care and Education, ECCE, Infants and Toddlers, Play-Based Learning, DAP, Parents’ Aspirations